Analysis of Scientific Literacy among Fifth-Grade Students in the Context of Ecological Citizenship - Windha Ana Sevia; Wahono Widodo; Andi Kristanto; Suryanti Suryanti (Journal of Learning Improvement and Lesson Study, 2026)
This study aimed to analyze the scientific literacy of fifth-grade students at SDN Airlangga I/198 Surabaya within the framework of ecological citizenship, operationalized through four dimensions; (1) ecological foundations, (2) conceptual awareness, (3) investigation and evaluation, and (4) action skills. A mixed-methods descriptive design was conducted involving 30 fifth-grade students through purposive sampling. Data were collected using a validated 10-item multiple-choice scientific literacy test aligned with three PISA indicators; explaining phenomena scientifically (SL1), evaluating and designing scientific enquiry (SL2), and interpreting data and evidence scientifically (SL3). The qualitative data gathered through classroom observations and semi-structured interviews. Data were analyzed using descriptive statistics for the test results and thematic analysis for observational and interview data. The results showed a moderate overall mean score (52.3%), with SL1 and SL3 also categorized as moderate (56.7% and 57.5%, respectively), while SL2 was notably low (41.0%). These findings indicate that students performed better in explaining scientific phenomena and interpreting data, while inquiry-related skills remained limited. Observations and interviews also revealed that students had basic conceptual understanding but still lacked analytical and inquiry skills. This study provides a foundational assessment linking scientific literacy and ecological citizenship at the elementary level in Indonesia, addressing a gap in existing research.